Concurrent Enhancement of Ductility and Efficiency for Annealing High‐Speed Steel via Tuning Cooling Rates. Issue 6 (25th February 2021) - Zhou, Xuefeng; Xia, Sheng; Liu, Zilin; Tu, Yiyou; Fang, Feng; Jiang, Jianqing
Abstract : High‐speed steel usually uses very slow cooling rates for complete annealing to guarantee good ductility at the expense of sacrificing the production efficiency. Herein, the aim is to probe the full potential of elevating cooling rates in simultaneous enhancement of ductility and efficiency. The results show that higher cooling rates produce finer ferrite grains and larger‐fractioned eutectoid carbides, which evolve from granular M6 C to rod‐shaped M23 C6 . The precipitate evolution originates from a transition of eutectoid transformation mechanism from a divorced mode to a lamellar manner due to upgraded undercoolings. Granular carbides display an excellent strain‐hardening ability compared with the rod‐shaped counterparts. Highly dispersive granular precipitates and fine ferrite grains formed under appropriate cooling conditions may contribute to larger work hardening rates and higher ductility. For the investigated M42 steel, cooling rates in the range of 2–5 °C min −1 can enhance the annealing efficiency while promising good ductility. Abstract : The conventional complete annealing uses very slow cooling rates to guarantee good ductility of high‐speed steel, but sacrifices the production efficiency. Herein, the desirable annealing microstructure for ductility enhancement is probed and it demonstrates that elevating cooling rates may simultaneously enhance the ductility and efficiency. The findings may shed more light in the development of novel high‐efficiency annealing processes.